Peningkatan Kemampuan Pemahaman Konsep Limbah Anorgranik Melalui Video Animasi Edukatif Berbasis Visual Auditori Kinestetik : Improving Conceptual Understanding of Inorganic Waste Through Visual-Auditory-Kinesthetic-Based Educational Animated Videos - Soemaryanti Ramadhani; Rendy Roos Handoyo (ITScience (Information Technology and Science), 2026)
This study aims to improve the learning process and understanding of inorganic waste concepts among Grade VIII students at risk of learning difficulties through the implementation of educational animated videos based on the Visual-Auditory-Kinesthetic (VAK) model. The study was motivated by students' limited ability to recognise characteristics, classify types, and explain differences regarding inorganic waste—issues stemming from instructional media that lacked interactivity and failed to provide concrete, engaging learning experiences aligned with students' learning characteristics. The study employed the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The subjects were 27 Grade VIII students, with a specific focus on six students at risk of learning difficulties. Data were collected through observation, tests, and documentation, then analysed using quantitative and qualitative descriptive techniques. The results indicate that the implementation of VAK-based educational animated videos successfully enhanced student learning activities across visual, auditory, and kinesthetic aspects. Visual activity increased from 57% to 76%, auditory activity from 61% to 83%, and kinesthetic activity from 66% to 91%. This increase in learning activity led to improved understanding of inorganic waste concepts, with all students achieving mastery by the end of Cycle II. Thus, the implementation of VAK-based educational animated videos proved effective in enhancing the quality of the learning process and the understanding of inorganic waste concepts among students at risk of learning difficulties.